Are Territorial Use Rights in Fisheries (TURFs) sufficiently large?. (April 2017) - Aceves-Bueno, Eréndira; Cornejo-Donoso, Jorge; Miller, Steve J.; Gaines, Steven D.
Abstract: Territorial Use Rights in Fisheries (TURFs) are gaining renewed attention as a potential tool for sustainable fisheries management in small-scale fisheries. This growing popularity comes despite the fact that there are still unresolved questions about the most effective TURF designs. One of the key questions is the role of TURF size in their efficacy both from ecological and social standpoints. This study explores the expected effects of existing TURF sizes on yields for TURF systems in Chile, México and Japan. The expected effect of larval dispersal and adult movement on yields was simulated for TURFs in each system. The results show that the analyzed TURF systems fall into three main categories: (a) TURFs that are of adequate size to eliminate the expected negative effects of both adult and larval movement, (b) TURFs that are large enough to eliminate the expected negative effects of adult movement, but not the effects of larval dispersal, and c) TURFs that are too small to eliminate the expected impacts on yield of both adult and larval movement. These analyses suggest that either existing models of TURF performance are incomplete or that there is significant scope for improved performance with altered TURF designs. Considering these alternatives, empirical evidence from the TURFs deemed too small suggests that complementary management tools can enhance TURF performance when natural or social constraints prevent the construction of TURFs of optimal size. Highlights: The effect of spillover on TURF yields was simulated for TURFs in Chile, Mexico and Japan. TURF size in all case studies is small in relation to the dispersal capacity of the targeted species. The high levels of spillover are expected to drive over-exploitation, still most cases show a strong performance. Possible explanations for the mismatch between observed TURF sizes and modeled optimal size were identified.